Ultrasound-Assisted Preparation of Chitosan/Nano-Activated Carbon Composite Beads Aminated with (3-Aminopropyl)Triethoxysilane for Adsorption of Acetaminophen from Aqueous Solutions - Vakili, Mohammadtaghi; Amouzgar, Parisa; Cagnetta, Giovanni; Wang, Baozhen; Guo, Xiaogang; Mojiri, Amin; Zeimaran, Ehsan; Salamatinia, Babak (MDPI, 2019)
A composite chitosan/nano-activated carbon (CS-NAC) aminated by (3-aminopropyl) triethoxysilane (APTES) was prepared in the form of beads and applied for the removal of acetaminophen from aqueous solutions. NAC and APTES concentrations were optimized to obtain a suitable adsorbent structure for enhanced removal of the pharmaceutical. The aminated adsorbent (CS-NAC-APTES beads) prepared with 40% w/w NAC and 2% v/v APTES showed higher adsorption capacity (407.83 mg/g) than CS-NAC beads (278.4 mg/g). Brunauer-Emmett-Teller (BET) analysis demonstrated that the surface area of the CS-NAC-APTES beads was larger than that of CS-NAC beads (1.16 times). The adsorption process was well fitted by the Freundlich model (R2 > 0.95), suggesting a multilayer adsorption. The kinetic study also substantiated that the pseudo-second-order model (R2 > 0.98) was in better agreement with the experimental data. Finally, it was proved that the prepared beads can be recycled (by washing with NaOH solution) at least 5 times before detectable performance loss. © 2019 by the authors.